The impact of relationship marketing practices on companies’ market and financial performance in emerging markets - Rebiazina, Vera (2024)
Purpose: The paper aims to reveal the impact of relationship marketing (RM) practices adopted by companies in emerging markets on their market and financial performance (FP) over a long-term, 13-year perspective. Design/methodology/approach: The research design combines primary empirical data from 229 Russian companies, based on the Contemporary Marketing Practices (CMP) survey, and objective FP data from official statistical databases for 2008–2020 to verify the impact of RM practices on market and FP in the long term. Findings: The research underlines the significant impact of RM practices. It is important to notice that the effect of product development (PD) on marketing performance is mediated by competitor orientation. PD affects market and FP, whose roles vary with the return on assets (ROA). Research limitations/implications: Research design supplements the subjective survey data with the objective FP data on the ROA to avoid common method bias. Practical implications: Implementation of RM practices by Russian companies can increase their effectiveness of performance in the long term. Originality/value: This research shows the positive impact of RM practices on the FP of Russian firms over the past 13 years.